The Mapping of Electronic Commerce Issues and Consumer Protection Policy in Indonesia - Muhammad Mufti Mubarok (Journal of Economics, Business, & Accountancy Ventura, 2021)
In the post-economic crisis in 1998, Indonesia experienced significant economic growth. Public consumption activities have become vulnerable due to open economic activities. In this case, the government has issued Law Number 8 of 1999 concerning Consumer Protection to protect consumers in fulfilling their needs. In September 2020, the Central Statistics Agency recorded that the millennial generation and generation Z dominate the population structure in Indonesia. This population structure also changes consumption patterns due to their lifestyle, including trends in electronic commerce or e-commerce. This study explores how consumer incidents relate to electronic commerce or e-commerce activities. It also strives to see the government’s role in formulating policies related to consumer protection in electronic commerce or e-commerce. This study used the descriptive qualitative method of policy analysis. The findings of this study indicate that responsive policies are needed to minimize consumer incidents and strengthen cross-ministerial/institutional coordination related to consumer protection with ministries/agencies coordinating consumer protection.